Pengembangan Media Menggunakan Aplikasi Book Creator pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Sulastri, Juliana; Anita, Yesi; Reinita, Reinita; Ahmad, Syafri (Asian Journal of Early Childhood and Elementary Education, 2024)
This research is motivated by the use of technology in the learning process which can provide a positive influence that can increase teaching effectiveness and learning achievements. Media Book Creator can increase students' learning motivation and can create a meaningful and enjoyable learning atmosphere for students. The aim of this research is to develop media using the Book Creator Application for Learning Pancasila Education in Elementary Schools that is valid, practical and effective. The type of research used is Research and Development (R&D) with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The subjects of this research were class IV students at SDN 11 Bukit Apit Puhun for the trial school and SDN 02 Pilot Bukittinggi for the research school. Data from this research were obtained from validation sheets, practicality sheets, and pretest-posttest scores. The validation results were 90% for material experts, 95% for language experts and 90% for media experts in the very valid category. The results of the practicality test at the trial school on the teacher response questionnaire got a percentage of 95% in the very practical category and the results of the practicality test of the student response questionnaire got a percentage of 95.9% in the very practical category. Meanwhile, the results of the practicality test in the research school on the teacher response questionnaire got a percentage of 97.5% in the very practical category and the practicality test results of the student response questionnaire got a percentage of 96.6% in the very practical category. The effectiveness test results obtained a result of 90.2% in the very high category. Thus it can be concluded that the media using the Book Creator application in Pancasila Education Learning in Elementary Schools is valid, practical and effective in use.